MACROECONOMIC IMBALANCE PROCEDURE IN THE EURO AREA – EX POST ANALYSIS - Ivana Šikulová (European Scientific Journal, ESJ, 2015)
Macroeconomic imbalances increase the probability of economic crisis, even more so in a monetary union with limited economic policy tools available. In the Economic and Monetary Union (EMU, euro area or eurozone), macroeconomic imbalances have accumulated since the euro introduction and they have significantly contributed to the emergence of the recent crisis with serious impacts on several Member States and hereby on the whole euro area. In order to improve the proper functioning of the EMU and prevent possible future crisis, a governance reform has been undertaken in the European Union (EU) in 2011, including introduction of a new procedure for preventing and correcting macroeconomic imbalances - the Macroeconomic Imbalance Procedure (MIP). It starts with an alert mechanism based on a set of eleven macroeconomic indicators with their threshold values (the so-called scoreboard), which this paper mainly focuses on. The first part of the paper provides an overview on the functioning of the preventive and corrective arm of the new procedure within the EU. The second part deals with the economic reasons for establishing respective MIP indicators. Finally, the third part aims to test appropriateness of the composition of the scoreboard for anticipation of the recent crisis by analysing the development of the indicators in the twelve euro area countries in period 2004-2007, i.e. prior to the outbreak of the crisis.